An Analysis of "Sell in May and Go Away" Strategy in Latin American Stock Markets. Issue 3 (3rd July 2022) - Almeida, Juliano Ribeiro de; Bergmann, Daniel Reed; Ferreira Savoia, José Roberto; Almeida, Guilherme Ribeiro de; Braga, Marina Arantes
Abstract: We carry out an in-depth analysis of patterns in stock market returns in seven Latin American countries to identify the presence and persistence of the "sell in May and go away" strategy. We use a predictive ability test to consider data snooping problems and the statistical interference of rules based only on historical asset prices. In line with the efficient market hypothesis, our results show that a trading strategy based on the Halloween effect never offered a significantly superior investment strategy than a "buy and hold" benchmark strategy in Latin American countries.